2014
DOI: 10.3109/0886022x.2014.934179
|View full text |Cite
|
Sign up to set email alerts
|

The role of disparities and socioeconomic factors in access to kidney transplantation and its outcome

Abstract: Background: Research focused on identifying vulnerable populations and revealing specific risk factors for barriers along the pathway from ESRD to kidney transplantation has been mostly descriptive and the causes of existing disparities remain unclear. However, several socio-economic factors that are associated with the access to and the outcome of the kidney transplantation have been identified. Summary: While the presence of racial, gender, and geographic disparities is noted, we were interested mostly to de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 78 publications
0
17
0
Order By: Relevance
“…Despite a decades‐long presence in the Twin Cities, the Hmong population remains uniquely vulnerable to healthcare disparities because of their linguistic and cultural isolation, and there is little published data on any immigrant transplant outcomes. With regards to obstacles in ESRD care and the KT evaluation process, a low socioeconomic status, cultural and linguistic isolation, and a general detachment from Western medical care have been partly attributed to inferior outcomes in such vulnerable populations . To date, there are no descriptions on the outcomes after KT in the U.S. Hmong community.…”
Section: Discussionmentioning
confidence: 99%
“…Despite a decades‐long presence in the Twin Cities, the Hmong population remains uniquely vulnerable to healthcare disparities because of their linguistic and cultural isolation, and there is little published data on any immigrant transplant outcomes. With regards to obstacles in ESRD care and the KT evaluation process, a low socioeconomic status, cultural and linguistic isolation, and a general detachment from Western medical care have been partly attributed to inferior outcomes in such vulnerable populations . To date, there are no descriptions on the outcomes after KT in the U.S. Hmong community.…”
Section: Discussionmentioning
confidence: 99%
“…Some of these clearly differ across race and have been associated with outcomes in transplantation. 2628 Medication nonadherence was not accounted for, which may impact racial disparities as well. 2931 Genetic factors, including gene variants in the donor (APOL1) and recipient (CYP P450 3A5) are more common in NHBs and have been associated with kidney transplant outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…If successful, these interventions may go a long way in reducing the racial disparity that has existed in kidney transplant since its inception. 2,8,11 …”
Section: Discussionmentioning
confidence: 99%
“…The social adaptability index (SAI) has been developed as a scoring mechanism that quantifies a patient’s SES based on five domains, including education level, employment status, marital status, income level and substance abuse. 11 Research has demonstrated that the SAI is a major risk determinant for health outcomes for diabetes, 12 CKD, 13 ESRD 14 and access to transplant; 15 more recently, one study demonstrated that a low baseline SAI score increased the risk of graft loss post-transplant. 16 However, to date, there is a lack of studies analyzing the impact of follow up SAI score on post-transplant outcomes and assessing if these associations differ by race.…”
Section: Introductionmentioning
confidence: 99%